P38 Changes in oral health behaviour between childhood and adolescence: findings from a UK cohort. (13th September 2016) - Leary, S; Graham, E; Do, L
Abstract : Background: Poor oral health can affect the ability to eat, speak and socialise normally, and can also be associated with serious health problems including cardiovascular disease and adverse pregnancy outcomes. Oral health behaviour may change throughout a person's life, but the stage from childhood to adolescence is critical as influences from peers increase while those from parents and other family members decrease. To our knowledge no studies have investigated changes in oral health behaviour between childhood and adolescence using repeated measurements on the same group of people. Methods: This study used data on 1862 participants from the Avon Longitudinal Study of Parents and Children (ALSPAC) who completed dental questionnaires at ages 7.5, 10.5 and 17.5 years. Associations between age and oral health behaviours (tooth brushing, dental attendance and beverage consumption) were assessed using random effects logistic regression models; models were fitted by gender if required. Results: Frequency of tooth brushing was associated with age in both genders (p = 0.01 for both); the odds ratio (95% confidence interval) for brushing teeth at least twice a day per year of age was 0.96 (0.94, 0.99) in males, and 1.03 (1.01, 1.06) in females. Electric toothbrush usage decreased with age for both genders (p < 0.001 for both), with a slightly larger decrease in females [0.82 (0.80, 0.84)] compared to males [0.87 (0.84, 0.90)]. There was no evidence of association between age and frequency of dental attendance in males [0.96 (0.78, 1.18), p = 0.7], whereas in females attendance increased with age [1.22 (1.03, 1.44), p = 0.02]. As there was no evidence of gender interactions with age, males and females were analysed together for beverage consumption. Fizzy drink and juice consumption increased with age [1.39 (1.23, 1.57) and 1.33 (1.24, 1.43) respectively, p < 0.001 for both), whereas there was no change in water consumption with age [1.00 (0.92, 1.09), p = 0.96]. Conclusion: Changes in oral health behaviour between childhood and adolescence have been demonstrated in this cohort; these findings can be used by healthcare professionals to plan healthcare interventions for improving oral health.